Effects of the Problem-Oriented Learning Model on Middle School Students’ Computational Thinking Skills in a Python Course - Bai, Hongquan; Wang, Xin; Zhao, Li (Frontiers in Psychology, 2021)
The rapid development of computers and technology affects modern daily life. Individuals in the digital age need to develop computational thinking (CT) skills. Existing studies have shown that programming teaching is conducive to cultivating students’ CT, and various learning models have different effects on the cultivation of CT. This study proposed a problem-oriented learning (POL) model that is closely related to programming and computational thinking. In all, 60 eighth-grade students from a middle school in China were divided into an experimental group (EG) which adopted the POL model, and a control group (CG) which adopted the lecture-and-practice (LAP) learning model. The results showed that the students who were instructed using the POL model performed better than those who were instructed using the LAP model in CT concepts, CT practices, and CT perspectives. There were significant differences in CT concepts and CT perspectives, but there was no significant difference in CT practices. The findings have implications for teachers who wish to apply new learning models to facilitate students’ CT skills, and the study provides a reference case for CT training and Python programming teaching.